Evaluation of the Washington, DC, Superior Court Drug Intervention Program, 1994-1998 - Harrell, Adele V. ([Verlag nicht ermittelbar], 2000)
This study was undertaken to measure the impact of the standard, treatment, and sanction dockets, which comprise the Superior Court Drug Intervention Program (SCDIP), on drug-involved defendants in Washington, DC, while examining defendants' continued drug use and substance abuse, criminal activity, and social and economic functioning. Features common to all three dockets of the SCDIP program included early intervention, frequent drug testing, and judicial involvement in monitoring drug test results, as well as the monitoring of each defendant's progress. Data for this study were collected from four sources for defendants arrested on drug felony charges between September 1, 1994, and January 31, 1996, who had been randomly assigned to one of three drug dockets (sanction, treatment, or standard) as part of the SCDIP program. First, data were collected from the Pretrial Services Agency, which provided monthly updated drug testing records, case records, and various other administrative records for all defendants assigned to any of the three dockets. Second, data regarding prior convictions and sentencing information were collected from computer files maintained by the Washington, DC, Superior Court. Third, arrest data were taken from the Uniform Crime Reporting Program. Lastly, data on self-reported drug use, criminal and personal activities, and opinions about the program were collected from interviews conducted with defendants one year after their sentencing. Variables collected from administrative records included drug test results, eligibility date for the defendant, date the defendant started treatment, number of compliance hearings, prior conviction, arrest, and sentencing information, and program entry date. Survey questions asked of each respondent fell into one of seven categories: (1) Individual characteristics, such as gender, age, and marital status. (2) Current offenses, including whether the respondent was sentenced to probation, prison, jail, or another correctional facility for any offense and the length of sentencing, special conditions or restrictions of that sentence (e.g., electronic monitoring, mandatory drug testing, educational programs, or psychological counseling), whether any of the sentence was reduced by credit, and whether the respondent was released on bail bond or to the custody of another person. (3) Current supervision, specifically, whether the respondent was currently on probation, the number and type of contacts made with probation officers, issues discussed during the meeting, any new offenses or convictions since being on probation, outcome of any hearings, and reasons for returning back to prison, jail, or another correctional facility. (4) Criminal history, such as the number of previous arrests, age at first arrest, sentencing type, whether the respondent was a juvenile, a youthful offender, or an adult when the crime was committed, and whether any time was served for each of the following crimes: drug trafficking, drug possession, driving while intoxicated, weapons violations, robbery, sexual assault/rape, murder, other violent offenses, burglary, larceny/auto theft, fraud, property offenses, public order offenses, and probation/parole violations. (5) Socioeconomic characteristics, such as whether the respondent had a job or business, worked part- or full-time, type of job or business, yearly income, whether the respondent was looking for work, the reasons why the respondent was not looking for work, whether the respondent was living in a house, apartment, trailer, hotel, shelter, or other type of housing, whether the respondent contributed money toward rent or mortgage, number of times moved, if anyone was living with the respondent, the number and ages of any children (including step or adopted), whether child support was being paid by the respondent, who the respondent lived with when growing up, the number of siblings the respondent had, whether any of the respondent's parents spent any time in jail or prison, and whether the respondent was ever physically or sexually abused. (6) Alcohol and drug use and treatment, specifically, the type of drug used (marijuana, crack cocaine, other cocaine, heroin, PCP, and LSD), whether alcohol was consumed, the amount of each that was typically used/consumed, and whether any rehabilitation programs were attended. (7) Other services, programs, and probation conditions, such as whether any services were received for emotional or mental health problems, if any medications were prescribed, and whether the respondent was required to participate in a mental health services program, vocational training program, educational program, or community service program.